Direct measurement of pressure-independent aqueous humour flow using iPerfusion. (September 2017) - Madekurozwa, Michael; Reina-Torres, Ester; Overby, Darryl R.; Sherwood, Joseph M.
Abstract: Reduction of intraocular pressure is the sole therapeutic target for glaucoma. Intraocular pressure is determined by the dynamics of aqueous humour secretion and outflow, which comprise several pressure-dependent and pressure-independent mechanisms. Accurately quantifying the components of aqueous humour dynamics is essential in understanding the pathology of glaucoma and the development of new treatments. To better characterise aqueous humour dynamics, we propose a method to directly measure pressure-independent aqueous humour flow. Using the iPerfusion system, we directly measure the flow into the eye when the pressure drop across the pressure-dependent pathways is eliminated. Using this approach we address i) the magnitude of pressure-independent flow in ex vivo eyes, ii) whether we can accurately measure an artificially imposed pressure-independent flow, and iii) whether the presence of a pressure-independent flow affects our ability to measure outflow facility. These studies are conducted in mice, which are a common animal model for aqueous humour dynamics. In eyes perfused with a single cannula, the average pressure-independent flow was 1 [-3, 5] nl/min (mean [95% confidence interval]) (N = 6). Paired ex vivo eyes were then cannulated with two needles, connecting the eye to both iPerfusion and a syringe pump, which was used to impose a known pressure-independent flow of 120 nl/min into the experimental eye only. The measured pressure-independent flow was then 121 [117, 125] nl/min (N = 7), indicating that the method could measure pressure-independent flow with high accuracy. Finally, we showed that the artificially imposed pressure-independent flow did not affect our ability to measure facility, provided that the pressure-dependence of facility and the true pressure-independent flow were accounted for. The present study provides a robust method for measurement of pressure-independent flow, and demonstrates the importance of accurately quantifying this parameter when investigating pressure-dependent flow or outflow facility. Highlights: We report the first direct measurement of net pressure-independent AH flow ( Q 0 ). Q 0 is the difference between aqueous humour inflow and pressure-independent outflow. In enucleated mouse eyes, Q 0 = 0, in contrast with previous estimates. When a known Q 0 is imposed, we can measure it accurately (within 10 nl/min). Inaccurate assessment of Q 0 leads to significant errors when measuring facility.